Perancangan Fasilitas Tunggu dan Advertising dengan Fleksibilitas Konfigurasi untuk Pusat Perbelanjaan - Amadea Belina Permatasari (Intra, 2017)
Design is inspired from Joshua Alim Santoso's final project which raised waiting activity phenomenon performed by shopping center visitors. Waiting is an activity which can reduce commercial transaction. Therefore waiting and advertising facility which can accommodate visitor’s and tenant’s needs is needed. Shopping center has a different area. Configuration flexibility is needed so that the product can be placed in several types of shopping center’s area. In this design, Ciputra World Mall, Pakuwon Mall, and Grand City Mall and Convex are chosen as study cases. The used design thinking process is design thinking by Tim Brown, CEO of IDEO with 9 stages. The stages are understand, observe, POV, ideate, prototype, test, story telling, pilot, and BMC. Concept design is oriented to meet the needs of visitor and tenant which are contradictory. The result is waiting and advertising facility consist of 3 module with each function. This module can be configured into linear, and centered to be placed in different area. Moreover, the modules are designed in such way to possible adding decoration elements based on each shopping center’s style. Next, the product can be expanded for commercial orientation for other shopping mall.